The impact of an integrated value chain intervention on household poultry production in Burkina Faso: Evidence from a randomized controlled trial - Leight, Jessica; Awonon, Josue; Pedehombga, Abdoulaye; Ganaba, Rasmané; Martinez, Elena M.; Heckert, Jessica; Gelli, Aulo (International Food Policy Research Institute, 2020)
This article reports on a cluster-randomized controlled trial conducted in 120 villages in rural Burkina Faso evaluating a multifaceted intervention (SELEVER) that seeks to increase poultry production by delivering training in conjunction with the strengthening of village-level institutions providing veterinary and credit services to poultry farmers. The intervention is evaluated in a sample of 1,080 households surveyed following two years of program implementation. Households exposed to the intervention significantly increase their use of poultry inputs (veterinary services, enhanced feeds, and deworming), and report more poultry sold and higher revenue; however, there is no evidence of an increase in profits. This evidence is consistent with the hypothesis that the return to inputs in the poultry market may not be sufficient to counterbalance the market costs of these inputs.